2021
DOI: 10.3389/fimmu.2020.549473
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Stromal Cells From Different Draining Areas Distinctly Regulate the Development of Chronic Intestinal Inflammation

Abstract: The balance between the responsiveness of the intestinal immune system and the gut environment is fundamental for the maintenance of intestinal homeostasis, which is required for an adequate recognition of entering antigens. The disruption of this homeostasis by exaggerated immune response to harmless antigens can lead to the development of intestinal disorders such as inflammatory bowel disease. Stromal cells are sessile non-hematopoietic cells that build the backbone of the lymph node, an important site for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Limited data are available on MLN and PPs in humoral responses, as well as on the implication of lymph node stroma in IBD pathophysiology [67,68,71,73,83,84,90,91,94]. While lymphatic obstruction by granulomas in MLNs and lymphatic vessels correlates with disease severity [2,10,[123][124][125], data on the role of lymphangiogenesis in disease activity are contradictory [116,117,[120][121][122].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data are available on MLN and PPs in humoral responses, as well as on the implication of lymph node stroma in IBD pathophysiology [67,68,71,73,83,84,90,91,94]. While lymphatic obstruction by granulomas in MLNs and lymphatic vessels correlates with disease severity [2,10,[123][124][125], data on the role of lymphangiogenesis in disease activity are contradictory [116,117,[120][121][122].…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model of intestinal autoimmunity, MLN stromal cells could partially promote T-cell tolerance by reducing only the CD8 + autoreactive T-cells [89]. Additionally, in mice with colitis, peripheral LN stromal cells were more tolerogenic and ameliorated the disease, compared to MLN stromal cells, which demonstrated a more proinflammatory profile [90].…”
Section: The Involvement Of the Lymphatic System Stromal Components I...mentioning
confidence: 99%
“…In the gut mucosa, immune cells can be found in organized secondary lymphoid structures, collectively known as gut-associated lymphoid tissue, as well as in intestinal tissue draining mesenteric lymph nodes (mLN), embedded between surface epithelial cells, and within the underlying connective tissue [1]. Research has shown that immune cells in secondary lymph nodes play an important role in the progression of IBD [23]. Therefore, we further analyzed the changes in the proportion of immune cells in the mLN of each group by flow cytometry.…”
Section: Ifn-γ-and Kyna-primed Hadscs Promoted Polarization Of M2 Mac...mentioning
confidence: 99%
“…Compared with healthy mammary epithelial cells, breast cancer cells also displayed upregulated surface CXCR4 and CCR7 receptors [92,93] (specific for CXCL12 and CCL19/CCL21, respectively) [94,95]. CXCL12, CCL19, CCL21, and CXCL16 are all expressed by LNSCs and are important for directing lymphocyte homing [94,96,97]; they might therefore also attract and coordinate cancer cell migration and invasion. Moreover, analysis of human breast cancer LNs has provided evidence that the reorganization of HEVs in pre-metastatic LNs is associated with aberrant secretion of CCL21 in perivascular FRCs compared with cancer-free LNs [98].…”
Section: In Cancer Lnscs Can Favor Immune Evasion and Metastasismentioning
confidence: 99%